Organizational Culture, Psychological Empowerment, and Job Satisfaction in the Implementation of the Independent Curriculum - Nunik Pujiyanti; S. Martono; Haryono Haryono; Suwito Eko Pramono (Universitas Negeri Semarang, 2023)
The implementation of an independent curriculum is identified as an educational strategy that can improve the quality of learning and student independence. His approach gives students the freedom to organize and direct their education. A strong organizational culture and psychological empowerment are essential in achieving optimal job satisfaction and successfully implementing the Merdeka Curriculum. This paper reviews the concept of school culture and how it can affect organizational performance. Psychological empowerment is crucial in creating a conducive work climate and encouraging students' active participation in the Merdeka Curriculum. The relationship between job satisfaction and implementing the Merdeka Curriculum is explored, emphasizing how job satisfaction can affect student engagement in independent learning. The method used is a literature study that combines findings from various relevant sources. In addition to interviews and direct observations at several schools implementing the Independent Curriculum. The results showed that an organizational culture that supports and strengthens psychological empowerment contributes to higher job satisfaction among educators and students. In addition, increasing job satisfaction also positively impacts the effective implementation of the Independent Curriculum because students who are satisfied with their learning experience will be more motivated and actively involved in the learning process. This paper presents the importance of building an organizational culture that supports psychological empowerment and job satisfaction so that the Independent Curriculum is successful.